2020
DOI: 10.32570/ijofe.696583
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Eating Attitude Disorder in Adolescents on Subjective WellBeing, Depression, Anxiety and Stress

Abstract: The aim of this study is to examine the relationship between eating attitude disorder, subjective well-being, depression, anxiety and stress on adolescents. For this purpose, 482 adolescents have been reached. In the research, "Eating Attitude Test", "Subjective Well-Being Scale" and "Depression, Anxiety and Stress Scale" were used as data collection tools. SPSS and AMOS package programs were used in the analysis of the data. A positive correlation was found between eating attitude disorder and depression, anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…2020;Field, 2013). In addition, another study conducted with adolescents in our country showed a high association between anxiety and depression (r=0.718, p<0.01) (Demir ve Kumcağız, 2020). Since, for example, an individual cannot perform their daily functionality during the process of depression.…”
Section: Comorbiditymentioning
confidence: 66%
See 1 more Smart Citation
“…2020;Field, 2013). In addition, another study conducted with adolescents in our country showed a high association between anxiety and depression (r=0.718, p<0.01) (Demir ve Kumcağız, 2020). Since, for example, an individual cannot perform their daily functionality during the process of depression.…”
Section: Comorbiditymentioning
confidence: 66%
“…2020;Field, 2013). Yine ülkemizde ergenlerle yapılan başka bir çalışmada ise anksiyete ve depresyon arasında yüksek ilişki tespit edilmiştir (r=0.718, p<0.01)(Demir ve Kumcağız, 2020). 2021 depresyona eşlik eden aksiyete/anksiyeteye eşlik eden depresyon hastalarında durum dört grup olarak ayrılmıştır.…”
unclassified
“…According to the literature, subjective well-being in adolescents predicts the levels of self-esteem and optimism (Eryılmaz & Atak, 2011), having successful identity status (Eryılmaz & Aypay, 2011), social skills (Canbay, 2010), motivation to participate in the lesson (Eryılmaz and Aypay, 2011) and self-efficacy (Telef & Ergün, 2013) positively. On the other hand, it negatively predicts social anxiety (Baş & Dilmaç, 2019), depression (Alim, 2018), eating disorders (Demir and Kumcağız, 2020), irrational belief level (Kabasakal & Emiroğlu, 2020) and peer bullying, victimization of peer bullying (Kılınç & Uzun, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Bu grubun yaşadığı bu yüksek kaygı, hareketsiz yaşam, korku ve ruhsal bunalım nedeniyle yeme ve egzersiz alışkanlıkları değişebilir. Adölesanlarla yapılan bir çalışmada yeme tutum bozukluğu ile depresyon, anksiyete ve stres arasında pozitif yönde bir ilişki olduğu da belirlenmiştir 24 . Ayrıca, COVID-19 pandemisi nedeniyle okul, ders dışı etkinlikler, fiziksel aktivite, sosyal etkileşimler gibi birçok aktivitenin aniden kaybedilmesi gençleri obeziteyle karşı karşıya bırakmıştır 25,26 .…”
Section: Introductionunclassified